EFEKTIVITAS LITERASI DIGITAL DALAM MENINGKATKAN PENDAPATAN UMKM DALAM PERSPEKTIF EKONOMI ISLAM (Studi Kasus UMKM Di Kelurahan Manggis Gantiang Kota Bukittinggi) - Fajri Azhari; Yenty Astarie Dewi (Adisam Publisher, 2024)
This study is driven by various phenomena observed in micro, small, and medium enterprises (MSMEs) located in Manggis Gantiang Village, Bukittinggi City. One such phenomenon is the limited comprehension among MSME actors regarding the existence of digital literacy within their enterprises. Initially, it was anticipated that digital literacy would augment the income of MSME actors; however, this did not transpire in an optimal manner, thereby hindering its effectiveness. Achieving the intended outcome was not possible. This study employs a qualitative methodology, gathering data through the utilisation of observational methods and interviews. Data analysis, meanwhile, employs the Miles and Huberman model. More specifically, conclusions, data reduction, and data presentation. Miles and Huberman's data analysis comprises the following stages: data reduction, data display, and conclusion drawing/verification. These stages are executed in an interactive manner and persist until completion, at which point the data becomes saturated. This study aims to determine, from an Islamic economic standpoint, the effect of digital literacy on the income of micro, small, and medium-sized enterprises (MSMEs) in Manggis Gantiang Village, Bukittinggi City. This study's findings demonstrate that digital literacy in Islamic economics does not increase the income of micro, small, and medium-sized enterprises (MSMEs) in Manggis Gantiang Village, Bukittinggi City. Specifically, nine out of fifteen merchants surveyed stated that digital literacy did not result in an increase in income. While there is an expectation that a rise in revenue will enable MSME participants to fulfil their operational obligations and subsequently assist others through the allocation of funds in accordance with Islamic economic principles.